Gambaran Resiliensi Pada Ibu yang Memiliki Anak Thalasemia - Melisa Falentina; Agoes Dariyo (Universitas Islam Tribakti Lirboyo Kediri, 2016)
When a child diagnosed with thalassemia, it can cause a pressure for parents and it can be a challenge especially for mother in running her role as a mother for their children. Patients with thalassemia need blood transfusions for the rest of his life, and it is require a expensive cost. This study aims to provide an overview of resilience in mothers of children with thalassemia. “Resilience is the human capacity to face, to cope, and to overcome the difficult times in life, so that someone be strengthened by experiences of adversity” (Grotberg, 1995). Resilience needs to be owned by a mother who has a child with thalassemia to be able to cope with sadness and rose to undergo their role as a mother. Data retrieval study using in-depth interview conducted towards four mothers (38 to 53 years old) who has a child with thalassemia. The result shows that the four subjects faced difficulties when they have the thalassemia children. Generally, the four subjects were able to build the resilience (I have, I am, I can) to cope the sadness, and able to perform their role as a mother very well